2022
DOI: 10.1007/s12571-022-01312-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, food insecurity and dietary diversity of households: Survey evidence from Nigeria

Abstract: The policy measures of the government of Nigeria to restrain the spread of COVID-19, particularly in the initial three months (April – June 2020) led to significant disruptions to household livelihoods and food security. We investigate the effects of COVID-19 on food security and dietary diversity of households; focusing on the pathways through which income loss, endowments of wealth, social capital, and safety net programs moderate the severity of households’ food security and dietary diversity. Primary data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 43 publications
4
18
1
Order By: Relevance
“…In addition, the FIES (Figure 1) showed that low income households are the most affected income category in terms of food insecurity experiences amid COVID-19 in the study areas in Nigeria. This result was corroborated by Balana et al, [18] who found that income losses further pushed Nigerian households into a more severe food insecurity level which is indicative of the challenges of achieving zero hunger (SDG 2) in Nigeria by 2030 [40,41]. It is recommended that the governments, particularly in the low-and lower-middle-income countries, should consider robust food supports and palliatives targeted at the poor and low-income earners, since these categories of individuals have experienced significantly reduced and compromised food quantity and quality [42][43][44].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In addition, the FIES (Figure 1) showed that low income households are the most affected income category in terms of food insecurity experiences amid COVID-19 in the study areas in Nigeria. This result was corroborated by Balana et al, [18] who found that income losses further pushed Nigerian households into a more severe food insecurity level which is indicative of the challenges of achieving zero hunger (SDG 2) in Nigeria by 2030 [40,41]. It is recommended that the governments, particularly in the low-and lower-middle-income countries, should consider robust food supports and palliatives targeted at the poor and low-income earners, since these categories of individuals have experienced significantly reduced and compromised food quantity and quality [42][43][44].…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, households experienced less food consumption and reduced quality. In addition, Balana et al [18] found out that income losses due to the devastating effect of COVID-19 have pushed more households in Nigeria into a more severe food insecurity status. In addition, the FIES (Figure 1) showed that low income households are the most affected income category in terms of food insecurity experiences amid COVID-19 in the study areas in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, the daily base calorie intake level reduces which does not fulfill the desire for good food. As a result, many families are suffering from severe health problems (Balana et al, 2022;Hoteit et al, 2022;Kundu et al, 2022: Ali, H., & Yasmin, Y. 2019.…”
Section: Introductionmentioning
confidence: 99%